The Influence of Educational Media via WhatsApp Group on Pregnant Women’s Ability for Early Detection of Preeclampsia in Pulau Tinggi Village - Yadriati Maya Pesa; Erika Erika; Wan Anita; Ummu Lutfiyah (International Journal of Health Sciences, 2025)
Preeclampsia remains one of the leading causes of maternal mortality in Indonesia and globally. Early detection is essential to prevent further complications. The use of digital media such as WhatsApp Groups has the potential to serve as an effective educational platform for pregnant women, particularly in rural areas with limited access to health information. Objective: To determine the influence of educational media delivered via WhatsApp Group on pregnant women’s ability to perform early detection of preeclampsia in Pulau Tinggi Village. Methods: This study employed a pre-experimental design with a one-group pretest–posttest approach. The sample consisted of 34 pregnant women who met the inclusion criteria, selected through total sampling. Educational interventions were provided through a WhatsApp Group for four weeks. The ability to detect preeclampsia early was measured using a validated questionnaire administered before and after the intervention. Data were analyzed using a paired t-test. Results: There was a significant increase in early detection ability after the educational intervention. The mean pretest score was 55.8 ± 7.9, increasing to 83.4 ± 6.8 in the posttest (p < 0.001). Knowledge categories also improved, with the proportion of respondents in the high category rising from 5.9% to 82.4%. Most respondents were aged 20–35 years, had a senior high school education, were multigravida, and were in the second trimester. Conclusion: Health education delivered via WhatsApp Group is proven effective in improving pregnant women’s ability to perform early detection of preeclampsia. This medium offers an accessible, low-cost, and sustainable alternative for maternal health education in rural communities.